Inclusive Identity to Improve Financial Literacy in A Community: Social Identity Perspective - Siskawati, Eka; Suwito, Suwito (KnE Social Sciences, 2024)
Financial inclusion programs are increasingly being echoed by the government at various levels of society. This program aims to open financial access and quality financial services for community groups who have not received it, so far. But in fact, financial inclusion programs are not balanced with increasing financial literacy in the community. One of the efforts made by village-level economic institutions (BUMNag) in implementing financial inclusion, while increasing the financial literacy of their communities is through community-based savings programs. This article analyzes the challenges in improving people’s financial literacy from a social identity perspective. The research uses a qualitative approach with a case study method. This research was conducted in a “Simpanan Bajapuik “ program at one of the Village Owned Enterprises (BUMNag) in West Sumatra. This research found that “Simpanan Bajapuik” is a program implemented with an individual empowerment approach in helping people get community-based financial access. In addition, this article finds that identity conflicts are the main obstacle in implementing the “Simpanan Bajapuik” program. From the perspective of social identity, this article analyzes the active participation of community members in the “Simpanan Bajapuik” program that can overcome multiple identity conflicts experienced by other community members. This article contributes to explaining aspects of the relationship between individuals and between groups, in the process of financial inclusion and increasing financial literacy through the “Simpanan Bajapuik” program policy. Keywords: financial inclusion, financial literacy, financial management, social identity theory